Epidemiological profile of Echinococcosis in Morocco from 2014 to 2018: case of Tangier-Tetouan-Al Hoceima Region - Nabah Kaoutar (EDP Sciences, 2021)
In Morocco, the National Hydatidosis Control Program has approved considerable progress. However, updating epidemiological profile data of the disease is necessary. This study is carried out to explore the characteristics and epidemiological profile of Hydatidosis in Tangier-Tetouan-Al-Hoceima region. We conducted a retrospective descriptive study from 28 April 2019 to 18 February 2020. The data collected covering 2014-2018 period from the program reports. The statistical analysis was performed by EpiInfo 7. In total, 94 cases were notified. In 2015, we recorded the highest incidence (0.83 cases/100.000 inhabitants). The highest percentage of patients was in Tetouan (28,7%). 54.3% of cases were women and 57.4% were from rural areas. The age of 47,3% of the cases was [18-40[years. The association between the professional status and sex was statistically significant (p<0.05). 94.4% of cases, in the first stage of infection, were diagnosed by ultrasound. 84.7% presented hepatic localization. Almost all cases (98.9%) were treated surgically. In conclusion, the National Hydatidosis Control Program should direct the actions in rural areas where the living conditions of the population are precarious. The study of canine Hydatidosis will also be necessary in the context of environmental health to carry out an integrated control for the human Hydatidosis disease.